Separate spatial soliton pairs in a biased series photorefractive crystal circuit with both the linear and quadratic electro-optic effects. Issue 6 (26th March 2017) - Jiang, Qichang; Su, Yanli; Nie, Hexian; Ma, Ziwei; Li, Yonghong
Abstract: We investigate the separate spatial soliton pair supported by both the linear and quadratic electro-optic effects. The numerical solutions of the bright–bright, dark–dark and bright–dark separate spatial soliton pairs are deduced from the coupling equations. The intensity profiles, coupling effects and dynamical evolutions of three types of separate spatial soliton pairs are analysed by numerical method. The two solitons in bright–bright separate spatial soliton pair can affect each other only by adjusting the background beam intensity. In dark–dark soliton pair, the two solitons can affect each other by adjusting the soliton beam intensity besides the background beam. And in bright–dark soliton pair, the bright soliton can affect the dark soliton only by the background beam intensity but the dark soliton can affect the bright soliton by both the background beam and soliton beam intensity.